Estimating the Effects of Milk Inspections on Infant and Child Mortality, 1880-1910 - D. Mark Anderson; Kerwin Kofi Charles; Michael McKelligott; Daniel I. Rees (Institute of Labor Economics (IZA), 2021)
In the mid-19th century, the urban milk supply in the United States was regularly skimmed or diluted with water, reducing its nutritional value. At the urging of public health experts, cities across the country hired milk inspectors, who were tasked with collecting and analyzing milk samples with the goal of preventing adulteration and skimming. Using city-level data for the period 1880-1910, we explore the effects of milk inspections on infant mortality and mortality among children under the age of 5. Event-study estimates are small and statistically insignificant, providing little evidence of post-treatment reductions in either infant or child mortality.
Keywords: I18; J1; N31; 330; mortality transition; milk inspections; infant mortality; child mortality; public health